Comparison and analysis for edge detection algorithms based on SQI image enhancement - Guanghui Deng; Zengli Liu (The 27th Chinese Control and Decision Conference (2015 CCDC), 2015)
Edge detection is an important role in image processing. The article examines several classical edge detection operator based on SQI image enhancement algorithm, for example, Roberts, Sobel, Prewitt, LOG, Canny. And, it analyses its performance and characteristics, and algorithm simulation by MATLAB. This paper compared with ordinary detection operator literature, after complete the image enhancement, its effect is better with selecting detection operator of image processing, and that will help. On the one hand, the experiment was carried out on the edge detection operator performance, on the other hand, the comparison and analysis to have a need to provide theory according to subjects.